Risk Response Strategies in the Supply Chain: Examining Attributes of Stakeholders and Risk Attitude - LIM, Shu Jian (Institutional Knowledge at Singapore Management University, 2010)
Supply chain management is about managing flows of material, information and funds in a complex network of entities of suppliers, manufacturers, distributors and customers. Companies are now connected in this network as an extended enterprise and any company may be involved in more than one such extended enterprises. But, such a network of relationships is very much vulnerable to disruptions of all sorts ranging from internal to inter-firm and to external turbulences. Companies now need to be prepared for risks associated with their participation in the supply chain network. Not many works in the literature have used theories to study supply chain risk management (SCRM). Only a handful of papers can be found to have used theories but even these authors confined to only studying supply risks. In this thesis, we aim to study both supply and demand risks due to suppliers and customers of a focal firm. As suppliers and customers have been recognized to be stakeholders with respect to the focal firm, we propose to use ‘stakeholder theory’ to investigate the question of how stakeholder attributes influence the decision made by managers on the choice of the risk response strategies. We also plan to explore the moderating effect of risk attitudes of the managers on the risk response decisions. Using data provided by managers from over 200 Singapore firms, we found support for some of the attributes relationships among risk attitude and partial relationships among risk attitude, stakeholder attributes, and risk response strategies. Factor analysis identified two groups of risk response strategies: process and buffer oriented risk response strategies. By examining the attributes contributing to manager’s decision to pursue either one or both of the risk response strategies, this study has important implications to firms in managing their stakeholders.